Mitigating Risk and Magnifying Protection: The Impacts of a Gang Intervention and Exiting Program on Criminogenic Risk Factors - Wong, Jennifer S. (Criminal justice and behavior, 2025)
Rates of gang-related violence are high across Canada, with one quarter of homicides in 2022 connected to gangs. Individuals face numerous risk and protective factors which influence the gang disengagement process; addressing these factors is key for successful interventions. The Gang Intervention and Exiting Program (GIEP) is a holistic case management program operating in British Columbia, Canada, which targets entrenched gang members and high-risk individuals. Using a retrospective, longitudinal, single group design, the current study used generalized estimating equations to examine changes in client risk and protective factors over time. Results indicate several short-term improvements in the areas of employment, substance use behaviors, engagement with prosocial peers and family, decreased association with criminally involved family and peers, and time spent in non-gang-related activities. These findings support the use of a multipronged case management approach using a combination of civilian and law enforcement service providers to encourage gang avoidance and exit.